Identifying Mechanisms of Normal Cognitive Aging Using a Novel Mouse Genetic Reference Panel - Dunn, Amy R.; Hadad, Niran; Neuner, Sarah M.; Zhang, Ji-Gang; Philip, Vivek M.; Dumitrescu, Logan; Hohman, Timothy J.; Herskowitz, Jeremy H.; O’Connell, Kristen M. S.; Kaczorowski, Catherine C. (Frontiers in Cell and Developmental Biology, 2020)
Developing strategies to maintain cognitive health is critical to quality of life during aging. The basis of healthy cognitive aging is poorly understood; thus, it is difficult to predict who will have normal cognition later in life. Individuals may have higher baseline functioning (cognitive reserve) and others may maintain or even improve with age (cognitive resilience). Understanding the mechanisms underlying cognitive reserve and resilience may hold the key to new therapeutic strategies for maintaining cognitive health. However, reserve and resilience have been inconsistently defined in human studies. Additionally, our understanding of the molecular and cellular bases of these phenomena is poor, compounded by a lack of longitudinal molecular and cognitive data that fully capture the dynamic trajectories of cognitive aging. Here, we used a genetically diverse mouse population (B6-BXDs) to characterize individual differences in cognitive abilities in adulthood and investigate evidence of cognitive reserve and/or resilience in middle-aged mice. We tested cognitive function at two ages (6mo and 14mo) using y-maze and contextual fear conditioning. We observed heritable variation in performance on these traits (h2RIx̄ = 0.51-0.74), suggesting moderate to strong genetic control depending on the cognitive domain. Due to the polygenetic nature of cognitive function, we did not find QTLs significantly associated with cognitive function or cognitive decline at the genome-wide level. To more precisely interrogate the molecular regulation of variation in these traits, we employed RNAseq and identified gene networks related to transcription/translation, cellular metabolism, and neuronal function that were associated with working memory, contextual fear memory, and cognitive decline. Using this method, we nominate the Trio gene as a modulator of working memory ability. Finally, we propose a conceptual framework for identifying strains exhibiting cognitive reserve and/or resilience to assess whether these traits can be observed in middle-aged B6-BXDs. Though we found that earlier cognitive reserve evident early in life protects against cognitive impairment later in life, cognitive performance and age-related decline fell along a continuum, with no clear genotypes emerging as exemplars of exceptional reserve or resilience— leading to recommendations for future use of aging mouse populations to understand the nature of cognitive reserve and resilience.